Notes on the pleasing lacewing genus Dilar Rambur, 1838 (Neuroptera, Dilaridae), with description of a new species from Vietnam - Martins, Caleb Califre; Flint, Oliver S., Jr.; Liu, Xingyue (Zootaxa, 2018)
In recent years many studies have been undertaken on the species of the genus Dilar Rambur, 1838 that occur in Asia, these have greatly increased the knowledge of Dilaridae in that region. Dilar has 69 valid species distributed in the Palaearctic and Oriental regions. In this paper we describe a new species Dilar aspoeckorum sp. nov. from Vietnam and a new female (probably Dilar harmandi (Navás, 1909)) from Nepal.